Studies on phytochemical and antimicrobial activity in pisonia grandis R. Br. - SUDHARAMESHWARI.K; SUGANYA.M; SALINI.R (International Journal of Pharma and Bio Sciences, 2018)
In the present study, phytochemical screening and antimicrobial activity of Pisonia grandis R.Br. have been studied. The P. grandis crude extracts were prepared by using different solvents (ethanol, methanol, acetone, chloroform and ethyl acetate).The phytochemical screening shows the presence of secondary metabolites such as alkaloids, phenols, sterol, flavonoids, diterpenes, cardiac glycosides, coumarins, tannins, steroids, terpenoids and saponin. Alkaloids, glycosides and terpenoids were absent in acetone, chloroform and ethyl acetate extract. Saponin was extracted in all solvent except Methanol. All phytoconstituents are present in ethanol extract. Antimicrobial activity was done against eight pathogenic bacteria [two are Gram positive (Bacillus subtilis and Staphylococcus aureus) and six are Gram negative (E. coli, Proteus vulgaris, Pseudomonas aeruginosa and Lactococcus lactis, Micrococcus and Serratia marcescens)].The antimicrobial activity was determined by Kirby–Bauer test and zone of inhibition was measured in cm. In all extract T1 shows high activity than T2. Among all the extract, ethanol showed good antimicrobial activity against all tested organisms next followed by methanol extract.